Poverty and Labor Market Change: Canada in Comparative Perspective - Shelley Phipps (Luxembourg Income Study (LIS), 1994)
The link between labor markets and poverty in Canada, Australia, Sweden, and the US is examined. An interesting examination of Australian minimum-wage rates and the experience of young workers is also contained.
Keywords: 330